Antimicrobial allergy 'labels' drive inappropriate antimicrobial prescribing: lessons for stewardship. (18th February 2016) - Trubiano, J. A.; Chen, C.; Cheng, A. C.; Grayson, M. L.; Slavin, M. A.; Thursky, K. A.
Abstract: Background: The presence of antimicrobial allergy designations ('labels') often substantially reduces prescribing options for affected patients, but the frequency, accuracy and impacts of such labels are unknown. Methods: The National Antimicrobial Prescribing Survey (NAPS) is an annual de-identified point prevalence audit of Australian inpatient antimicrobial prescribing using standardized definitions of guideline compliance, appropriateness and indications. Data were extracted for 2 years (2013–14) and compared for patients with an antimicrobial allergy label (AAL) and with no AAL (NAAL). Results: Among 21 031 patients receiving antimicrobials (33 421 prescriptions), an AAL was recorded in 18%, with inappropriate antimicrobial use significantly higher in the AAL group versus the NAAL group (OR 1.12, 95% CI 1.05–1.22, P < 0.002). Patterns of antimicrobial use were significantly influenced by AAL, with lower β-lactam use (AAL versus NAAL; OR 0.47, 95% CI 0.43–0.50, P < 0.001) and higher quinolone (OR 2.07, 95% CI 1.83–2.34, P < 0.0001), glycopeptide (OR 1.59, 95% CI 1.38–1.83, P < 0.0001) and carbapenem (OR 1.74, 95% CI 1.43–2.13, P < 0.0001) use. In particular, among immunocompromised patients, AAL was associated with increased rates of inappropriate antimicrobial use (OR 1.68, 95% CI 1.21–2.30, P = 0.003), as well as increased use of quinolones (OR 1.88, 95% CI 1.16–3.03, P = 0.02) and glycopeptides (OR 1.82, 95% CI 1.17–2.84, P = 0.01). Conclusions: AALs are common and appear to be associated with higher rates of inappropriate prescribing and increased use of broad-spectrum antimicrobials. Improved accuracy in defining AALs is likely to be important for effective antimicrobial stewardship (AMS), with efforts to 'de-label' inappropriate AAL patients a worthwhile feature of future AMS initiatives.